Self-Medication Behavior of Dental Students with Oral Ulceration Lesions: A Cross-Sectional Study in Yogyakarta, Indonesia - Iriana, Fita Fathaya; Susanto, Hendri; Amalia, Rosa (Journal of Dentistry Indonesia, 2025)
Objective: Self-medication refers to medication behavior for self-diagnosed symptoms. Oral ulcers are self-medicated lesions in the oral cavity. Dental students have different knowledge about oral cavity lesions and may self-medicate using drugs. This study aimed to determine the self-medication behavior of dental students for oral ulcers. Methods: This cross-sectional study was conducted on dental students in the Faculty of Dentistry from different batch years. Purposive sampling was used to select students with oral ulcer lesions in the last six months. A validated and reliable questionnaire was used to assess self-medication behavior. Data collection using the online form. Student behavior data were presented descriptively and analyzed using a one-way ANOVA test. Results: The mean of self-medication behavior for oral ulcers was observed to be higher for the earliest intake group (2015–2016) of students than for the middle (2017–2018) or most recent (2019–2020) year groups. The results of the one-way ANOVA test showed that the p-value was not significant between the groups of dental students. Conclusion: No difference was observed in the self-medication behavior for oral ulcers among dental students based on their study year.